ANALYSIS OF NITRATE, PHOSPHATE AND CONCENTRATION ABILITY OF DIATOM (Bacillariophyta) PLANKTONIK IN THE SUMATERA PROVINCE OF WEST NIRWANA BEACH - Tampubolon, Theresia; Nurrachmi, Irvina; Nedi, Syahril (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2019)
This research was conducted in August 2018 with the aim to determine the concentration of nitrate and phosphate in the waters of Nirwana Beach, find out the type and abundance of diatoms found in the waters of Nirwana Beach, and determine the relationship of nitrate and phosphate concentrations to diatoms in Nirwana Beach waters. Determination of sampling location using purposive sampling, namely by taking into account the conditions and conditions of the research area. Sampling of nitrate and phosphate using a sample bottle measuring 100 ml then given preservatives and diatom samples using a bucket and filtered with plankton net no.25 and preserved with 4% lugol solution as much as 3-4 drops and analysis was carried out at the Marine Chemistry and Marine Biology Laboratory , Faculty of Fisheries and Marine Affairs, University of Riau. The results showed nitrate concentration in Nirwana Beach waters ranging from 0.5 mg / l - 0.3 mg / l. And phosphate concentration in the waters of Nirwana Beach ranges from 0.19 mg / l - 0.08 mg / l. In the coastal waters of Nirvana there are 16 species of diatoms found. The highest abundance of diatom species from all species found was Cosconidiscus sp with an average of 4263 ind / l per station. While the lowest abundance of species is Melosira sp, Thalassionema sp, Neodelphinies sp, Rhizossolenia sp and Cocconeis sp with an average of 73.5 ind / l. Diatom diversity index (H ') in Nirwana Beach waters is classified as moderate and community stability is categorized as moderate, there is no type that dominates the uniformity index (E) Nirwana Beach waters are still balanced and there is no competition for food or places. and phosphate with an abundance of diatoms which in this case means that the higher the concentration of nitrate and phosphate, the more abundance of diatoms.